A medical insurance fund operation performance evaluation system under the DRG payment mode reform - Wang, Zijian; Chang, Weifu; Luo, Aijing (Frontiers in Public Health, 2025)
BackgroundAn evaluation system for comprehensively measuring medical insurance fund operational performance under China’s Diagnosis Related Groups (DRG) payment reform holds critical theoretical and practical significance, especially for enhancing the efficiency of medical insurance fund utilization and the quality of healthcare services. However, few studies undertake performance evaluations of medical insurance funds under DRG payments, especially those incorporating the Analytic Hierarchy Process (AHP)-Entropy Weight Method (EWM)- Fuzzy Comprehensive Evaluation (FCE) method model.MethodsThis study utilizes operational data from medical insurance funds across eight cities in S Province, China, from 2020 to 2022. It develops an innovative performance evaluation system for medical insurance funds utilizing the AHP-EWM-FCE evaluation method. Finally, it explores the key influencing factors by applying the Tobit regression model.ResultsAs the reform of DRG payment methods has advanced, the operational performance scores related to the management, fundraising, utilization, and satisfaction of DRG medical insurance funds have consistently improved. Notably, the comprehensive indexes of QD and JN cities exhibit significant comparative advantages, resulting in higher performance evaluation scores for their medical insurance funds. Additionally, the performance scores assessed by the proposed evaluation system align closely with actual operational outcomes. Regression analysis further indicates that medical service capability is the key determinant influencing the operational performance of medical insurance funds.ConclusionThis study develops a novel evaluation system for measuring medical insurance funds’ operational performance. The insights can help proactively foster the high-quality development of these funds, and modernization of the medical insurance governance system and governance capabilities; stimulate the fund’s productivity; and enhance the health and wellbeing of people.